Isolation and Identification of Acid-Forming Bacteria in Arabica Coffee Fruit (Coffea arabica) During Wet Fermentation - Qothrunnada Amira Salma; Sarkono Sarkono; Aida Muspiah (Jurnal Penelitian Pendidikan IPA, 2024)
The distinctive flavor and aroma possessed by Arabica coffee are an attraction for coffee enthusiasts. Post-harvest processing of coffee such as coffee fruit fermentation also contributes to the formation of the flavor and aroma of Arabica coffee. In this study, spontaneous fermentation was conducted by adding distilled water, with treatments on fermentation days 4 and 7 aimed at detecting acid-forming bacteria that played a role in the fermentation process. The bacterial isolates were characterized through macroscopic and microscopic observations, physiological, and biochemical tests. Identification of bacterial isolates was performed using the profile matching method based on Bergey’s Manual of Systematic Bacteriology (Holt et al., 1994) and Axellson (2004) until the genus level. The identified bacterial genera were Asaia, Gluconobacter, Neoasaia, Saccharibacter, and Lactobacillus.